Progesterone receptor membrane component 1 reduces cardiac steatosis and lipotoxicity via activation of fatty acid oxidation and mitochondrial respiration - Sang R. Lee (Nature Portfolio, 2021)
Abstract Obesity is implicated in cardiovascular disease and heart failure. When fatty acids are transported to and not adequately oxidized in cardiac cells, they accumulate, causing lipotoxicity in the heart. Since hepatic progesterone receptor membrane component 1 (Pgrmc1) suppressed de novo lipogenesis in a previous study, it was questioned whether cardiac Pgrmc1 protects against lipotoxicity. Hence, we focused on the role of cardiac Pgrmc1 in basal (Resting), glucose-dominant (Refed) and lipid-dominant high-fat diet (HFD) conditions. Pgrmc1 KO mice showed high FFA levels and low glucose levels compared to wild-type (WT) mice. Pgrmc1 KO mice presented low number of mitochondrial DNA copies in heart, and it was concomitantly observed with low expression of TCA cycle genes and oxidative phosphorylation genes. Pgrmc1 absence in heart presented low fatty acid oxidation activity in all conditions, but the production of acetyl-CoA and ATP was in pronounced suppression only in HFD condition. Furthermore, HFD Pgrmc1 KO mice resulted in high cardiac fatty acyl-CoA levels and TG level. Accordingly, HFD Pgrmc1 KO mice were prone to cardiac lipotoxicity, featuring high levels in markers of inflammation, endoplasmic reticulum stress, oxidative stress, fibrosis, and heart failure. In vitro study, it was also confirmed that Pgrmc1 enhances rates of mitochondrial respiration and fatty acid oxidation. This study is clinically important because mitochondrial defects in Pgrmc1 KO mice hearts represent the late phase of cardiac failure.